PEMBELAJARAN GALLERY WALK BERPENDEKATAN CONTEXTUAL TEACHING LEARNING MATERI SISTEM PENCERNAAN DI SMA - Widarti, Sri; Peniati, Endah; Widiyaningrum, Priyantini (Journal of Biology Education, 2013)
Penelitian ini bertujuan untuk mengetahui pengaruh pembelajaran Gallery walk berpendekatan CTL terhadap aktivitas dan hasil belajar siswa pada materi sistem pencernaan makanan di SMA Negeri 1 Gringsing. Jenis penelitian Quasi experimental dengan Control group pre test-post test design. Populasi yang sekaligus sampel yaitu kelas XI IPA yang terdiri dari kelas XI IPA1 dan XI IPA2. Variabel bebas berupa pembelajaran Gallery walk berpendekatan CTL materi sistem pencernaan makanan sedangkan variabel terikat adalah aktivitas dan hasil belajar siswa. Data penelitian berupa aktivitas siswa diambil dengan lembar observasi dan hasil belajar diambil dengan lembar penilaian soal. Data aktivitas siswa dianalisis secara deskriptif kuantitatif persentase sedangkan hasil belajar dianalisis dengan uji t. Hasil penelitian menunjukkan bahwa jumlah siswa kelas eksperimen yang sangat aktif dan aktif 81,06%, sedangkan kelas kontrol 58,91%. Rata-rata hasil belajar siswa kelas eksperimen sebesar 80,89 dengan ketuntasan klasikal 93,18% sedangkan kelas kontrolÂ  sebesar 74,08 dengan ketuntasan klasikal 55,81%. Hasil analisis menggunakan uji t menunjukkan terdapat perbedaan hasil belajar kelas eksperimen dan kelas kontrol. Kesimpulannya pembelajaran Gallery walk berpendekatan CTL berpengaruh positif terhadap aktivitas dan hasil belajar siswa pada materi sistem pencernaan di SMA Negeri 1 Gringsing. Â  Abstract ___________________________________________________________________ This study aimed to find out the effect of Gallery walk learning approaches and CTL upon the activities and the studentsâ learning outcomes on digestive system materials at SMA Negeri 1 Gringsing. The research was Quasi experiment with Control group pre test-post test design. The population and its sample altogether were grade XI science students from grade XI IPA1 and XI IPA2. The independent variable was the Gallery walk learning approaches with CTL on digestive system materials while the dependent variables were the activity and the studentsâ learning outcomes. The data of research were student activity taken by observation sheet and studentsâ learning outcomes taken by question assessment sheet.Â Â  The data of students activity was analyzed by quantitatively descriptive percentage while the studentsâ learning outcomes were analyzed by t test. The result showed that number of students of experimental class who were very active and active were 81,06% while those of control class were 58,91%. The average of result studentsâ learning outcomes of experimental class was 80,89 with classical completeness 93,18% and that of control class was 74,08 with classical completeness 55,81%. The analysis using T-test showed that there was difference between the result of learning between experimental class and control class. The conclusion was that Gallery walk learning approaches with CTL brought a positive effect on studentsâ activity and learning outcomes on digestive system learning materials at SMA Negeri 1 Gringsing.